Impact of trade policies on the MSMEs' competitiveness in Indonesia: The case of e-commerce import restrictions - Hasran; Rasya Athalla Aaron; Rayhan Fasya Firdausi (Center for Indonesian Policy Studies (CIPS), 2024)
The government's intention to create a fair e-commerce ecosystem for MSMEs by restricting imports through e-commerce has failed to achieve its original goals. While its positive impact remains unseen, it has closed the channels for some MSMEs to access foreign supplies. Instead of closing the official channel for MSMEs to engage with cross-border e-commerce, the government should eradicate any unfair competition practices. Under a fair business environment, MSMEs' success in benefiting from domestic and international trade will depend on their competitiveness.
Keywords: 330